Evaluation of Midkine Expression in Dentigerous Cysts, Odontogenic Keratocysts and Different Types of Ameloblastoma - Naghmeh JEIROODI; Mahshid BAGHERPOUR; Razieh ZARE; Shima TORABİ ARDAKANI; Azadeh ANDISHEH TADBIR (Federation of Turkish Pathology Societies, 2018)
Objective: Midkine is a heparin-binding growth factor whose expression is increased in most tumors, namely ameloblastomas. This study aimed to compare Midkine expression in different odontogenic lesions. Material and Method: This analytical cross-sectional study was performed on 52 definitely diagnosed odontogenic lesions including 15 dentigerous cysts, 13 odontogenic keratocysts, and 17 unicystic and 5 multicystic ameloblastomas archived from 1997 to 2015. Midkine expression was examined in tissue samples through immunohistochemistry. The nonparametric Kruskal-Wallis and Mann-Whitney tests were run as appropriate (P < 0.05). Results: The frequency of Midkine expression was < 20% in 7.7%, 20-50% in 25%, and > 50 % in 67.3% of the samples, indicating significant differences among the groups (P = 0.002). Moreover, the expression intensity was strong in 63.5%, moderate in 23.1%, and weak in 13.5% of odontogenic lesion samples (P = 0.071). The total staining score was weak in 3.8%, moderate in 48.1%, and strong in 48.1% of the cells, displaying significant differences between the study groups in this regard (P = 0.043). Conclusion: Midkine can be considered as both a differentiating factor and a molecular-targeted therapy in odontogenic lesions. Yet, further studies are required to approve the role of this cytokine in different biological and pathological stages of the tumors.